PENEGAKAN HUKUM DAN MORALITAS MANUSIA DALAM PERSPEKTIF FILOSOFI - Aturkian Laia (LPPM Universitas Nias Raya, 2023)
Law enforcement in this nation is still far from expectations, especially in terms of the moral quality possessed by law enforcers who are very messy and still maintain a corrupt mentality and this is very dangerous in realizing legal justice for all Indonesian people. Law enforcers are